Demystifying scholarly metrics a practical guide - Vinyard, Marc W.; Colvin, Jaimie Beth (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"Demystifying Scholarly Metrics gives librarians and faculty the confidence to navigate the maze of scholarly metrics, identify quality journals in which to publish, and measure the impact of scholarly works"--Provided by publisher.